Implementation of Dashboard Power Bi for Data Visualization of Graduates During Covid-19 Pandemic in The Faculty of Tarbiyah and Teaching Sciences IAIN Palopo - Mifta Zulfahmi Muassar (Journal of Information Technology and Its Utilization, 2022)
This study presents information regarding the distribution of graduates and the number of students who graduated during the pandemic of Covid-19 at the Faculty of Tarbiyah and Teaching Sciences IAIN Palopo through visualization of data depicted during the Covid19 pandemic, namely in a vulnerable time in 2020 to early 2022. This visualization is done by distributing graduate data into the Microsoft Power BI application and depicted in the form of a diagram, after that the data is visualized in the form of diagrams and numbers based on the categories that have been collected in the form of an Excel file which is then saved in a CSV file type so that the files obtained lighter than before so that the distribution of data in the form of information for graduates of the Faculty of Tarbiyah and Teaching Sciences at IAIN Palopo can be easily observed by policymakers in making decisions.